Plap-1/Asporin in the Periodontium: A Key Regulator of Oral Health - Senthil, Dharani; Narayane. R; Balu, Pratebha; Saravana Kumar. R (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
The periodontal ligament (PDL) is a unique, vascularized fibrous connective tissue responsible for anchoring teeth to the alveolar bone, facilitating mechanical functions such as chewing and contributing to tissue homeostasis, wound healing, and regeneration. PDL mainly consists of fibroblasts that create a network of main fibers connecting the cementum of the tooth root to the alveolar bone. Recently, Periodontal Ligament Associated Protein-1 (PLAP-1)/Asporin, a member of the small leucine-rich proteoglycan (SLRP) family, has emerged as a significant protein in the PDL, playing a vital role in maintaining tissue balance and regulating bone morphogenetic protein (BMP) signaling. (PLAP-1)/Asporin inhibits BMP-2 signaling, crucial for preventing abnormal bone formation, such as ankylosis. Furthermore, (PLAP-1)/Asporin distinctive 16-aspartic acid N-terminal sequence is essential for preserving periodontal tissue homeostasis. While its involvement in diseases such as periodontitis, osteoarthritis, cancers, and heart failure is being explored, the precise role of (PLAP-1)/Asporin in periodontal health remains under investigation. Emerging evidence connects (PLAP-1)/Asporin to periodontitis, indicating that this protein may act as a protective factor for periodontal health; however, further research is needed to fully understand its role. (PLAP-1)/Asporin levels as a biomarker of disease may indicate periodontal disease and systemic inflammation, improving diagnostics and treatment monitoring. Insights into how (PLAP-1)/Asporin affects tissue responses could aid in creating new therapies for enhancing periodontal healing and systemic health. This review explores the structure, function, and regulatory characteristics of PLAP-1/Asporin, emphasizing its potential as a protective factor in periodontal health and its broader implications for systemic diseases. Understanding (PLAP-1)/Asporin multifunctional role could open new avenues for innovative therapeutic approaches targeting periodontal and systemic conditions.